2017
DOI: 10.1002/hrm.21880
|View full text |Cite
|
Sign up to set email alerts
|

The problem of employees' network centrality and supervisors' error in performance appraisal: A multilevel theory

Abstract: This article reveals an unexplored paradox for HR managers: the centrality of an employee in the social network benefits performance but hampers performance appraisal because it affects supervisors' rating errors. Central employees can be erroneously rated high on performance even when they are not high performers because supervisors tend to overappraise their performance. A distinction is made between rating precision, which depends on supervisors' uncertainty regarding employees' performance, and rating accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 160 publications
(312 reference statements)
0
5
0
Order By: Relevance
“…The task performance item was, “Please respond to the following questions about how well you feel that you and your coworkers are performing the requirements of your jobs.” Each employee rated him/herself and coworkers on how well he or she felt he/she and each of their coworkers were performing on a seven‐point scale (1 = “Not Well at All”; 7 = “Extremely Well”). We used the mean of all raters as the measure of task performance to obtain a 360° evaluation as a way of reducing various performance rating biases including those possessed by supervisors when evaluating subordinates with high levels of network centrality (Bizzi, 2018). 2 On average, an employee had 10 performance ratings and 74.5% of ratings included the employee's direct supervisor 3…”
Section: Methodsmentioning
confidence: 99%
“…The task performance item was, “Please respond to the following questions about how well you feel that you and your coworkers are performing the requirements of your jobs.” Each employee rated him/herself and coworkers on how well he or she felt he/she and each of their coworkers were performing on a seven‐point scale (1 = “Not Well at All”; 7 = “Extremely Well”). We used the mean of all raters as the measure of task performance to obtain a 360° evaluation as a way of reducing various performance rating biases including those possessed by supervisors when evaluating subordinates with high levels of network centrality (Bizzi, 2018). 2 On average, an employee had 10 performance ratings and 74.5% of ratings included the employee's direct supervisor 3…”
Section: Methodsmentioning
confidence: 99%
“…Given that all performance appraisals are subject to human involvement, error and bias are constant threats to effective evaluation (Battaglio, 2015; DeNisi and Smith, 2014). Complementarily, Bizzi (2018) adds that performance ratings can be affected by two types of error. The first one relates to errors that supervisors make because they are uncertain about an employee performance (random error), as indicated by precision in performance ratings.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The second one relates to errors that supervisors make because they are biased in favor of or against an employee (systematic error), as indicated by accuracy in performance ratings. So, while the random error direction is unpredictable, the systematic error direction is predictable because a supervisor is biased in one specific direction, either in favor of or against certain employees (Bizzi, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Kuvaas (2006) suggested that assessment of employee is based upon his or her performance according to the requirement of market and demand of the organization. In order to enhance the efficacy of performance appraisal system, Bizzi (2018) proposed a multilevel theory, which also addressed the supervisor's error in performance appraisal system.…”
Section: Performance Appraisal and Employees' Performancementioning
confidence: 99%